Do Patients With Ewing's Sarcoma Continue With Sports Activities After Limb Salvage Surgery of the Lower Extremity?. Issue 3 (March 2015) - Hobusch, Gerhard Martin; Lang, Nikolaus; Schuh, Reinhard; Windhager, Reinhard; Hofstaetter, Jochen Gerhard
Abstract: Background: Limb salvage surgery has evolved to become the standard method of treating sarcomas of the extremities with acceptable oncologic results. However, little information exists relative to the activity level or ability to participate in sports after tumor reconstructions. Questions/purposes: The aims of the study were to answer the following questions: (1) Which sports activity levels and what types of sports can be expected in the long term after tumor reconstruction? (2) Which frequency durations are patients with Ewing's sarcoma able to perform in long‐term followup after local control? (3) Do surgical complications affect sports activity level? Methods: Thirty patients (13 females, 17 males; mean age, 18 ± 8 years; range, 2‐36 years at diagnosis; mean followup 16 ± 6 years [minimum, 5 years]) were included. Tumors were located in the pelvis, femur, tibia, and fibula. Surgical procedures included surgical resections alone (n = 8), surgical resection with biological reconstruction (n = 9), or endoprosthetic reconstruction (n = 13). We assessed UCLA sports activity levels, kinds of sports as well as the frequency per week and the duration of each training unit at long term (minimum followup, 5 years). Results: In long‐term followup 83% patients (25 of 30) were performing athletic activity regularly. The hours/week of sports depended on type of surgery and were highest after resections in the pelvis and femur (5.8) and were lowest after megaprosthetic reconstruction of the pelvis (1.0). Patients undergoing biologic reconstructions were able to perform high‐impact sports. UCLA sports activity levels were high after joint‐preserving vascularized fibula for tibia reconstruction (7.4) and after megaprosthetic reconstruction of the lower extremity (6.3‐6.4) and were low after tumors located in the fibula (4.2). Complications during followup did not significantly influence sports activity in long‐term survivors. Conclusions: Long‐term survivors can achieve high levels of sports activity in many instances. Tumor sites are associated with the postoperative sports activity levels. This information can help surgeons counsel patients in terms of athletic expectations after limb salvage reconstruction for patients with Ewing's sarcoma. Level of Evidence: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.